Sustainability and branchless banking: The development and validation of a distinct measurement scale. (November 2021) - Zahid, Muhammad; Rahman, Haseeb Ur; Ullah, Zabeeh; Muhammad, Ali
Abstract: This study aimed to develop and validate a new scale for measuring the sustainability and development of branchless banking. The study followed the scale development procedure based on Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) using SPSS 22 and Structural Equation Modelling (SEM) analyses through SmartPLS. The data was collected from 150 respondents from different stakeholders of branchless banking. The EFA reported with the seven-factor solution including social sustainability, product responsibility, economic sustainability, labor practices and decent work, environmental sustainability, human rights and ethics, and branchless banking development. The structural model further validated the positive impact of human rights and ethics, labor practice and decent work, product responsibility, and social sustainability on the development of branchless banking. The study has a novelty to develop and validate the first-ever scale for measuring sustainable branchless banking. Besides, the study also provides many theoretical and practical implications for different stakeholders including academia, researchers, top management of the banks, and practitioners. Highlights: Develop and validate a new scale to measure branchless banking sustainability. Examine the impact of sustainable branchless banking on its development. Recommendations to improve and develop sustainable branchless banking.